2001
DOI: 10.1161/01.hyp.38.1.71
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Job Stress but not Individual Cardiovascular Reactivity to Stress Is Related to Higher Blood Pressure at Work

Abstract: Abstract-Psychological stress has been reported to be related to higher blood pressure (BP) and unfavorable cardiovascular profile. However, because of the complexity of personal stress management, a multilevel stress measurement strategy is needed. The aim of this cross-sectional study was to analyze the respective influences of the subjective perception of professional strain (high demand and low latitude) and cardiovascular reactivity to a stress test (Stroop stress test) on BP. Worksite BP was measured in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 29 publications
0
30
0
3
Order By: Relevance
“…25 It has been shown that job stress is related to higher BP at work in normotensive subjects. 5,27 Another study showed that the BP response to daily stress was enhanced in hypertensive subjects compared with normotensive subjects. 28 Ambulatory BP during work was 10% higher than home BP in hypertensives, but the difference was only 3% in normotensives in this study.…”
Section: Diurnal Bp Variation In Relation To Mental and Physical Actimentioning
confidence: 99%
“…25 It has been shown that job stress is related to higher BP at work in normotensive subjects. 5,27 Another study showed that the BP response to daily stress was enhanced in hypertensive subjects compared with normotensive subjects. 28 Ambulatory BP during work was 10% higher than home BP in hypertensives, but the difference was only 3% in normotensives in this study.…”
Section: Diurnal Bp Variation In Relation To Mental and Physical Actimentioning
confidence: 99%
“…The basis for the observed increase in hypertension prevalence with increasing number of children is not well known, however, considering the socio-economic challenges facing families in Nigeria, there are indications that higher number of children will increase stress though the respondent monthly salary appear to increase with the number of children. Psychological stress has been related to higher blood pressure and unfavorable cardiovascular profile ( Fauvel et al, 2001), and there is moderate support for psychological factors as predictors of hypertension development, with the strongest support for anger, anxiety, and depression variables. Pooled effects for these factors are of sufficient magnitude to suggest potential clinical as well as statistical relevance (Rutledge and Hogan, 2002).…”
Section: A Sizeable Portion (146%) Of the Study Population Were Casementioning
confidence: 99%
“…These studies generally demonstrate that job strain is associated with increased BP throughout the day and night. [3][4][5][6][7][8][9][10][11] Further, there is a greater incidence of myocardial infarction in individuals who report high job strain. 12 Although, there is considerable evidence that job strain has adverse effects on BP, little work has been performed examining the physiological mechanisms underlying the relationship between job strain and BP.…”
mentioning
confidence: 99%